Antioxidant activity, phenolic and flavonoid contents in the leaves of different varieties of sweet potato (Ipomoea batatas) - Hue, S.M.; Boyce, A.N.; Somasundram, C. (2012)
The study of antioxidants from natural sources has gained popularity in the recent years. Six Ipomoea batatas leafy varieties namely Batu Kelantan, Batu Biasa, Biru Putih, Oren, Vitato and Indon were compared to assess the total phenols, flavonoids, reducing power and antioxidant activity. In this study, the Indon variety showed the highest level of total phenolic contents at 5.35 ± 0 g GAE/100 g DW. The flavonoid contents in the leaves ranged from 96 ± 47.6 μg/ g in Indon variety to 263.5 ± 43.5 μg/g in Batu Biasa variety. 1,1-diphenyl-2-picryl hydrazyl (DPPH) was used to determine the radical scavenging activity in leaves, in which the Indon and Biru Putih variety had the highest and lowest scavenging activities of 372.4 μg/ ml (IC50) and 597.61 μg/ ml (IC50), respectively. All varieties, except Biru Putih, showed the high radical scavenging activity compared to the ascorbic acid standard. Besides, all the leaf varieties also showed increment in their reducing power with increasing concentrations. Thus, Ipomoea batatas leaves can be used as a potential source of natural antioxidants.